PENGGUNAAN METODE COOPERATIVE LEARNING TIPE EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN MINAT BELAJAR IPS SISWA KELAS VIII MADRASAH TSANAWIYAH AT THOHIRIYAH SRI KAYANGAN KECAMATAN TANJUNG MEDAN KABUPATEN ROKAN HILIR - Kartikowati, Sri; Sabrus, Hardisem; ', Supartik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: The background of this study is that the students 'interest in learning IPS relatively low which is characterized by a sense of interest in the students' social studies, less the member's attention, a sense of curiosity of students. Besides, teachers using conventional methods, ie lectures and without the use of media so that students feel bored and berinplikasi on student interest. Of the necessary problem Action Research (PTK) by applying the learning method Kooperative Non Example Example Learning mode. This study aims to increase interest in social studies class VIII MTs At Thohiriyah Srikayangan districts Tanjung Medan. The population number of students as many as 30 students. This research was conducted in two cycles each cycle consisting of two meetings. Instrument of data collection in this study is the observation sheet teacher, student observation sheet and observation sheet student interest. The results of the analysis of the activity of teachers in the first cycle of 45% in the category enough, the second cycle increased to 83.3% lam very good category. While the results of the analysis of the activity of students in the first cycle of 58.3% in the category enough, the second cycle increased to 87.2% in the excellent category, activities of student interest cycle I 48.27% in the medium category and the second cycle has reached the level of success ie 87.45% in the high category. With concluded that if the implementation of cooperative learning methods Learning mode Non Example Example can be and improve the interest in social studies class VIII MTs At Thohiriyah Srikayangan district of Tanjung Medan.Keywords : Learning Method, Learning Kooperative, Non Example Example mode, IPS learned Interests